2020
DOI: 10.1371/journal.pone.0232509
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution and phylogenetic considerations in cuckoos (Aves, Cuculiformes, Cuculidae)

Abstract: The Cuckoos have a long history of difficult classification. The species of this order have been the subject of several studies based on osteology, behavior, ecology, morphology and molecular data. Despite this, the relationship between Cuculiformes and species of other orders remains controversial. In this work, two species of Cuculidae, Guira guira (Gmelin, 1788) and Piaya cayana (Linnaeus, 1766), were analyzed by means of comparative chromosome painting in order to study the chromosome evolution of this gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…The comparison of our results with the data of G . guira from dos Santos et al [ 30 ] suggests a very similar karyotype between these species, with several chromosomal rearrangements shared between both species ( Table 1 ). On the other hand, no chromosomal rearrangements were shared between these species and P .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The comparison of our results with the data of G . guira from dos Santos et al [ 30 ] suggests a very similar karyotype between these species, with several chromosomal rearrangements shared between both species ( Table 1 ). On the other hand, no chromosomal rearrangements were shared between these species and P .…”
Section: Discussionmentioning
confidence: 96%
“…Since the first reports, cytogenetic studies on cuckoos have revealed karyotype variation both in chromosomal number and morphology, with 2n ranging from 64 to 90 [ 28 , 29 , 30 ]. This indicates that interchromosomal rearrangements, such as fusion, fission, and intrachromosomal rearrangements, such as pericentric inversion and centromere repositions, have played an important role in the chromosome evolution of these species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations